Credit management systems and financial performance of savings and credit cooperatives (SACCOS) in mid-western Uganda - Kule, Baguma John Muhunga Kule; Kamukama, Nixon; Kijjambu, Nsambu Frederick (My University, 2020)
American Journal of Finance ISSN 2520-0445 (Online) Vol.5, Issue 1, pp 43-53, 2020 www.ajpojournals.org 43 CREDIT MANAGEMENT SYSTEMS AND FINANCIAL PERFORMANCE OF SAVINGS AND CREDIT COOPERATIVES (SACCOs) IN MID-WESTERN UGANDA Baguma John Muhunga Kule Mbarara University of Science and Technology, Faculty of Business and Management Sciences, Uganda Email: kule@must.ac.ug Assoc. Prof. Nixon Kamukama Mbarara University of Science and Technology Email: nkamukama@must.ac.ug Dr. Nsambu Frederick Kijjambu Mbarara University of Science and Technology Email: Nsambu.kijjambu@must.ac.ug ABSTRACT Purpose: To ascertain the relationship between credit management systems and financial performance of SACCOs in Mid-Western Uganda. Methodology: A cross-sectional research design and positivist paradigm were used to collect data from 93 SACCOs in Mid-Western Uganda using a closed-ended questionnaire. Standard linear regression analysis was carried out. Findings: The study findings reveal a moderate, positive and significant relationship between credit management systems and financial performance of SACCOs in Mid-Western Uganda. Unique contribution to practice and policy: This study suggests to management a need to put into place effective credit management systems if SACCOs are to improve their financial performance by ensuring that favorable terms and conditions, and adequate client appraisal process are in place. In addition, government should support SACCOs by providing staff trainings on credit terms and conditions formulation and improving their competencies in client appraisal
Keywords: Credit Management Systems; Financial Performance and SACCOs